The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3171/case2275
|View full text |Cite
|
Sign up to set email alerts
|

Arachnoid cyst alone causes hemifacial spasm: illustrative case

Abstract: BACKGROUND Hemifacial spasm (HFS) due to an arachnoid cyst at the cerebellopontine angle is rare. Here, the authors reported such a case and analyzed the mechanism of facial nerve hyperactivity by reviewing the literature. OBSERVATIONS A 40-year-old man presented with right HFS for the past 3 years. Preoperative magnetic resonance imaging revealed a right cerebellopontine angle cystic mass with high intensity on T2-weighted images, low intensity on T1-weighted and diffusion-weighted images, and no contrast e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…12 Although tumors such as epidermoid tumors, meningiomas, and acoustic neuromas, as well as cysts and aneurysms, have been associated with HFS, they are less frequently observed. [13][14][15] Yang et al 16 reported cases of HFS secondary to arachnoiditis caused by neurocysticercosis. Surprisingly, arachnoid bands have not previously been reported as a primary cause of HFS without any vessel involvement.…”
Section: Observationsmentioning
confidence: 99%
“…12 Although tumors such as epidermoid tumors, meningiomas, and acoustic neuromas, as well as cysts and aneurysms, have been associated with HFS, they are less frequently observed. [13][14][15] Yang et al 16 reported cases of HFS secondary to arachnoiditis caused by neurocysticercosis. Surprisingly, arachnoid bands have not previously been reported as a primary cause of HFS without any vessel involvement.…”
Section: Observationsmentioning
confidence: 99%
“…However, within the context of tumors originating from the facial nerve, such as facial nerve schwannomas, reports of facial spasm presentation are conspicuously absent [29][30][31]. This discrepancy may be attributed to the propensity of facial nerve If LSR disappears before decompression or persists after decompression, careful exploration is warranted.…”
Section: Lsr Monitoring In Secondary Hfsmentioning
confidence: 99%
“…However, within the context of tumors originating from the facial nerve, such as facial nerve schwannomas, reports of facial spasm presentation are conspicuously absent [29][30][31]. This discrepancy may be attributed to the propensity of facial nerve schwannomas to originate, predominantly, from the peripheral aspect of the facial nerve rather than from its Life 2023, 13, 1825 9 of 12 intracranial segment.…”
Section: Lsr Monitoring In Secondary Hfsmentioning
confidence: 99%